2001
DOI: 10.1165/ajrcmb.25.1.4500
|View full text |Cite
|
Sign up to set email alerts
|

Liquid and Ion Transport by Fetal Airway and Lung Epithelia of Mice Deficient in Sodium-Potassium-2-Chloride Transporter

Abstract: Chloride (Cl(-)) movement across fetal lung epithelia is thought to be mediated by the sodium-potassium-2-Cl(-) cotransporter NKCC1. We studied the role of NKCC1 in Cl(-) and liquid secretion in late-gestation NKCC-null (-/-) and littermate control fetal mouse lung. NKCC -/- mice had decreased lung water compared with littermate controls (wet/dry: control, 8.01 +/- 0.09; NKCC -/-, 7.06 +/- 0.14). Liquid secretion by 17-d NKCC -/- distal lung explants was similar to control explants. Bumetanide inhibited basal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 40 publications
1
33
0
Order By: Relevance
“…In that study, Grubb and colleagues demonstrated that loop diuretics neither affected Cl Ϫ secretion under basal conditions, nor during forskolin-induced Cl Ϫ secretion. A minor role for the NKCC in pulmonary ion transport can also be deduced from reports that NKCC knockout animals develop normal lungs and do not exhibit obvious abnormalities concerning pulmonary ion transport properties and Cl Ϫ secretion, in particular (15). Interestingly, the present study observed a loop diureticsensitive current by establishing a Cl Ϫ gradient as achieved using apical Cl Ϫ -free solution.…”
Section: -Test)supporting
confidence: 73%
See 3 more Smart Citations
“…In that study, Grubb and colleagues demonstrated that loop diuretics neither affected Cl Ϫ secretion under basal conditions, nor during forskolin-induced Cl Ϫ secretion. A minor role for the NKCC in pulmonary ion transport can also be deduced from reports that NKCC knockout animals develop normal lungs and do not exhibit obvious abnormalities concerning pulmonary ion transport properties and Cl Ϫ secretion, in particular (15). Interestingly, the present study observed a loop diureticsensitive current by establishing a Cl Ϫ gradient as achieved using apical Cl Ϫ -free solution.…”
Section: -Test)supporting
confidence: 73%
“…AE activity was observed in various airway epithelia (11), as well as in alveolar type II pneumocytes (23). Further significance concerning the importance of HCO 3 Ϫ /Cl Ϫ exchanger in pulmonary Cl Ϫ transport is provided by studies using NKCC knockout mice (15). That study concluded that normal lung development in these animals might be due to the function of basolateral HCO 3 Ϫ /Cl Ϫ exchangers bypassing the loss of NKCC function.…”
Section: -Test)mentioning
confidence: 98%
See 2 more Smart Citations
“…The Cl − channels may participate in fluid secretion in fetal lungs since the lung undergoes a change from fluid secretion to absorption at birth. However, CFTR and NKCC knock-out mice were not fatal (Gillie et al, 2001;Snouwaert et al, 1992). In these mice, other Cl − channels may compensate for those channels.…”
Section: Significancementioning
confidence: 98%